Tweets of Iraqi Political Leaders Regarding The Movement to Form The Governmet Through Twitter (From 3rd Septemper 2018 To 3rd Septemper 2019) - Nima, Ola Jassim; Salim, Sahar Khalifa (ALBAHITH ALALAMI, 2020)
This research analyses the tweets of Iraqi politicians (leaders) that took place simultaneously with the formation of the Iraqi government after the elections in 2018. The formation of the Iraqi government was considered one of the most critical issues that emerged in the political process to which the Iraqi media as well as social networking sites paid considerable attention. In this regard, Iraqi political leaders have published many tweets concerning the formation of the government, some of them have caused great controversy in the political climate. As Twitter is one of the most digital platforms that have been widely used on the global scale in recent years, politicians have employed it to publish their opinions, ideas, and to exchange accusations against each other, as well as to deliver their messages to others in a direct and fast manner. Accordingly, the research has studied and analysed the tweets published by Iraqi Political Leaders regarding the formation of the Iraqi government for one year (i.e. from 3rd September 2018 to 3rd September 2019). This was carried out in order to address the research problem and to accomplish its main objectives by using the survey method and subsequently, by performing the content analysis tool during the study period. In the same regard, the research problem has been summarized through a set of questions, the most notable of which are as follows: (What are the topics formulated in the tweets of Iraqi political leaders?), (What are the prevailing political trends in the tweets of Iraqi political leaders towards the formation of the government?) and (Who are the parties addressed in the tweets of Iraqi political leaders?)